EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2017)
The editorial of Engenharia Térmica of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. Global energy demands are on the rise, and the current technology used to generate, transmit, and distribute electricity will not be able to meet the growth due to the bottlenecks in densely populated areas and the inefficiencies throughout the electrical grid. Soon, new technologies will be required to relieve the constraints on the grid while being cost effective, reliable, and environmentally acceptable. High temperature superconducting technology (HTS), that admits critical temperatures above 30 K, and under development, has the means to provide ways to overcome the challenges faced by electric utility companies. Other applications including all-electric ships and aircrafts would also benefit greatly from the use of HTS power devices in meeting the increasing electrical power requirements at high power densities. Therefore, advanced thermal engineering will be highly required to design and produce superconducting power generation systems and transmission lines that are technically and economically viable. The mission of Engenharia Térmica is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.